Hometown Hamburg : artisans and the political struggle for social order in the Weimar Republic - Domurad, Frank (Anthem Press, 2019)
Preface: Continuity in German history -- The peculiarity of German history : handicraft versus Handwerk -- Hamburg : a German home town? -- In search of Hamburg Handwerk : figures and forms -- The handicraft occupational estate in the crisis of the Weimar Republic -- A constitution without decision -- From the politics of barter to Volksgemeinschaft -- Conclusion: Continuity in German history revisited.